The impact of multidisciplinary team nutrition management on nutritional and toxicity status in patients with nasopharyngeal carcinoma - Xueqing Ou; Hui Chen; Ting Qiu; Yajun Yuan; Xiaohua Gong (Elsevier, 2023)
Objective: To explore the impact of multidisciplinary team (MDT) nutrition management on the nutritional and toxicity status of patients with nasopharyngeal carcinoma undergoing chemoradiotherapy. Methods: A total of 104 patients undergoing chemoradiotherapy for nasopharyngeal carcinoma admitted to our hospital from July 2018 to February 2021 were retrospectively enrolled, including who received conventional nutrition management (the routine group, n ​= ​52) and who received MDT nutrition management (the experimental group, n ​= ​52). Nutritional indicators (dietary intake, body mass index, serum albumin, serum prealbumin, hemoglobin, total lymphocyte count, serum transferrin [TRF]), the Nutrition Risk Screening 2002 (NRS2002) score and acute toxicity level were recorded before, during, and after chemoradiotherapy. Multiple regression analysis was performed to identify nutritional risk indicators. Results: During and after chemoradiotherapy, the body mass index, albumin, prealbumin, hemoglobin, total lymphocyte count, TRF, dietary intake, number of patients with an NRS2002 score < 3, and acute toxicity score in the experimental group improved compared to those in the routine group (P ​< ​0.05). Concurrent chemotherapy, the NRS2002 score and a half-diet strategy were independent factors affecting the nutritional status of nasopharyngeal carcinoma patients who underwent chemoradiotherapy. Conclusions: Active screening and evaluation of the nutritional status of patients with nasopharyngeal carcinoma during chemoradiotherapy as well as MDT nutrition management can be used to detect nutritional problems, thus improving quality of life and reducing related toxicity.